The principle of Islamic moderation (Wasatiyyah) as expounded in Tafsir al Azhar - Ahmad, Nadzrah; Amir, Ahmad Nabil (2015)
This paper will briefly analyze the fundamental principle of Islamic moderation (wasatiyyah) as illustrated in Tafsir al-Azhar. It attempts to discuss the ideas of balanced and an ecumenical community par excellence (ummah wasata) and the principle of moderate Islam as interpreted and propounded by Hamka (1908-1981) in his Tafsir. It will also look into Hamka’s other writings such as Pandangan Hidup Muslim (The Muslim’s Perspective), Keadilan Sosial dalam Islam (Social Justice in Islam)and Falsafah Hidup (The Philosophy of life)that further illustrated his understanding of this important idea and its significant implications in Muslim society.